Different ex Vivo and Direct in Vivo DNA Administration Strategies for Growth Hormone Gene Therapy in Dwarf Animals - Peroni, Cibele Nunes; Oliveira, Nélio Alessandro de Jesus; Cecchi, Claudia Regina; Higuti, Eliza; Bartolini, Paolo (IntechOpen, 2011)
None